2014
DOI: 10.1002/stem.1544
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibition with Valproic Acid Downregulates Osteocalcin Gene Expression in Human Dental Pulp Stem Cells and Osteoblasts: Evidence for HDAC2 Involvement

Abstract: Adult mesenchymal stem cells, such as dental pulp stem cells, are of great interest for cell-based tissue engineering strategies because they can differentiate into a variety of tissue-specific cells, above all, into osteoblasts. In recent years, epigenetic studies on stem cells have indicated that specific histone alterations and modifying enzymes play essential roles in cell differentiation. However, although several studies have reported that valproic acid (VPA)—a selective inhibitor of histone deacetylases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
143
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(157 citation statements)
references
References 43 publications
11
143
3
Order By: Relevance
“…22 The application of epigenetic regulators, such as inhibitors of histone modification enzymes, may be valuable for stem cell-based interventions. 23, 24 Previous studies showed that the degree of H3K9 acetylation and H3K4 trimethylation in MSCs increased, whereas the level of H3K9 trimethylation decreased during osteogenic differentiation, 25 which was in consistent with our results. For example, TSA, an inhibitor of HDAC1, promoted osteogenic differentiation by altering the epigenetic modifications on the Runx2 promoter in a BMP signaling-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…22 The application of epigenetic regulators, such as inhibitors of histone modification enzymes, may be valuable for stem cell-based interventions. 23, 24 Previous studies showed that the degree of H3K9 acetylation and H3K4 trimethylation in MSCs increased, whereas the level of H3K9 trimethylation decreased during osteogenic differentiation, 25 which was in consistent with our results. For example, TSA, an inhibitor of HDAC1, promoted osteogenic differentiation by altering the epigenetic modifications on the Runx2 promoter in a BMP signaling-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…The results revealed that the reduction of the proton concentration resulted in prominent increases in the expressions of BGLAP and IBSP (Fig. 1B), which are mainly expressed during late-stage osteogenic differentiation and mineralization2021; this latter phenomenon was also proved by the data in our study (Fig. S1).…”
Section: Resultssupporting
confidence: 79%
“…The expression of these markers (osteocalcin OCN, bone sialoprotein BSP, and dentin sialophosphoprotein DSPP) (Morsczeck et al, 2009;Batouli et al, 2003;Yang et al, 2012;Laino et al, 2011;Chen et al, 2012), is an evidence for the osteogenic/dentinogenic differentiation of DPSCs and SCAP. It has been reported recently that certain inhibitors could enhance the expression levels for osteoblast differentiation (OPN and BSP) in DPSC (Paino et al, 2014) selectively.…”
Section: Discussionmentioning
confidence: 99%